KESEPADANAN PENERJEMAHAN BAHASA PRANCIS KE DALAM BAHASA INDONESIA PADA KATEGORI BUDAYA (STUDI KASUS FILM POURRIS GÂTÉS) - Hasanah, Nadiyah; Gumilar, Dudung; Amalia, Farida (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
Translating a culture is difficult because the culture contained in the source language doesn’t necessarily find its equivalent in the target language. This research focuses on the equivalence analysis of cultural translation from French into Indonesian in the film Pourris Gâtés (2021) by Nicholas Cuche. The purpose of this study is to describe the acceptability and unacceptability of material culture translation contained in the film Pourris Gâtés (2021) which is reviewed and confirmed in 3 aspects, namely 1) based on the theory of translation equivalence assessment by Nababan and Nuraenin (2012). 2) in terms of translation ideology according to Venuti (2008). 3) Based on the type of modulation proposed by Vinay and Dalbernet (1995). The method used in this research i qualitative-descriptive by using listening and note-taking techniques. The results of this study show that the material culture category reviewed by (Newmark, 1988) is divided into 5 namely food/beverage, clothing, buildings, vehicles, and living equipment there are 50 case data containing material culture which there are 50 case data containing material culture which acceptable of 45 (90% case data of material culture in an acceptable manner and 5 (10%) case data containing material culture that less acceptable. Furthermore, 32 case data were found to use modulation types of translation procedures, while 18 case data were found to use translation of modulation types in the film pourris gâtés is done by translator so that the culture contained in the source language can be easily understood and equivalent in the target language (TL) even though it has to change the word structure